Synthesis, Structural and Thermal Studies of Dl-Alanine Potassium Di- Chromate Single Crystals - Ponmani, Sundararaj Lincy Mary; Gracelin, Soundararajan Gnanakkan Pushpalatha; Selvakumar, Somasundaram; Durai, Subbaiah Chelladurai Vella (Makara Journal of Science, 2024)
Amino acids and their complexes are organic or semiorganic materials that have attracted considerable attention because they can be easily used in optical storage devices. DL-alanine is one of the rare amino acids that crystallizes in anoncentrosymmetric group. This article demonstrates how DL-alanine potassium dichromate (DAPC) single crystals have shown sufficient growth. DAPC crystals were analyzed by single crystal X-ray diffraction and powder X-ray diffraction. Using thermogravimetric analysis/differential thermal analysis (TGA/DTA) and differential scanning calorimetry, this work also examined the melting point, thermal stability, decomposition point, and other thermal parameters of the DAPC crystals. Results show that the decomposition point of DAPC is 397 °C, which is analogous to that of TG/DTA. The dielectric constant, dissipation, and AC conductivity were also measured, and the results were analyzed to understand various features of the current operating model. The activation energy of the DAPC single crystal is 0.074 eV.